2009
DOI: 10.1002/poc.1569
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ortho substituents on carbonyl carbon 13C NMR chemical shifts in substituted phenyl benzoates

Abstract: Effect of ortho substituents on carbonyl carbon 13 C NMR chemical shifts in substituted phenyl benzoates Vilve Nummert a , Mare Piirsalu a , Vahur Mä emets a , Signe Vahur a and Ilmar A. Koppel a * 13 C NMR spectra of 37 ortho-, meta-, and para-substituted phenyl benzoates, containing substituents in benzoyl and phenyl moiety, 4 ortho-substituted methyl and 5 ethyl benzoates as well as 9 R-substituted alkyl benzoates have been recorded. The influence of the ortho substituents on the carbonyl carbon 13 C NMR ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 57 publications
3
42
0
Order By: Relevance
“…Recently we found [1,8] good correlations between the log k values of the alkaline hydrolysis of ortho-substituted phenyl benzoates and the infrared stretching frequencies of carbonyl group, ν CO , as well as the 13 C NMR chemical shifts, δ CO , in case the additional resonance and steric scales were included. The aim of the present paper was to check the applicability of the Charton equation to describe the influence of ortho substituents on the δ( 17 O) values in phenyl esters of orthosubstituted benzoic acids, (X-C 6 H 4 CO 2 C 6 H 5 ), and to compare the substituent effects in the δ( 17 O) values with those in the alkaline hydrolysis, [6] the infrared stretching frequencies, ν CO , [9] and the 13 C NMR chemical shifts, δ CO .…”
Section: The Values Of δ(mentioning
confidence: 99%
See 4 more Smart Citations
“…Recently we found [1,8] good correlations between the log k values of the alkaline hydrolysis of ortho-substituted phenyl benzoates and the infrared stretching frequencies of carbonyl group, ν CO , as well as the 13 C NMR chemical shifts, δ CO , in case the additional resonance and steric scales were included. The aim of the present paper was to check the applicability of the Charton equation to describe the influence of ortho substituents on the δ( 17 O) values in phenyl esters of orthosubstituted benzoic acids, (X-C 6 H 4 CO 2 C 6 H 5 ), and to compare the substituent effects in the δ( 17 O) values with those in the alkaline hydrolysis, [6] the infrared stretching frequencies, ν CO , [9] and the 13 C NMR chemical shifts, δ CO .…”
Section: The Values Of δ(mentioning
confidence: 99%
“…In the rigid systems the steric influence of ortho substituents was explained by the van der Waals interactions between the ester group and the adjacent bulky substituent. [41,42] In the previous papers we found that in substituted phenyl benzoates, (X-C 6 H 4 CO 2 C 6 H 5 , C 6 H 5 CO 2 C 6 H 4 -X) the influence of ortho substituents on the log k values in the alkaline hydrolysis, [1][2][3][4][5][6][7] the carbonyl carbon 13 C NMR chemical shifts, δ CO , [8] and the carbonyl carbon infrared stretching frequencies, ν CO , [9] was precisely described with the Charton equation [45] using the inductive, σ I , [8,46] resonance, σ°R, [8,47] and steric, E S B , [6,48] substituent constants. Nearly the same results were obtained when for ortho substituents the Charton steric scale, υ, [49] based on van der Waals radii, was used.…”
Section: The Values Of δ(mentioning
confidence: 99%
See 3 more Smart Citations